Current Issues of Suicidology 1988
DOI: 10.1007/978-3-642-73358-1_35
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Biogenic Amines and Metabolites in the CSF of Suicide Victims and Nonsuicides

Abstract: The use of registered names, trademarks, etc. in this publication does not imply, even in the absence of a specific Statement, that such names are exempt from the relevant protective laws and regulations and therefore free for general use. Product liability: The publisher can give no guarantee for information about drug dosage and application thereof contained in this book. In every individual case the respective user must check its accuracy by Consulting other pharmaceutical literature. Typesetting, printing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…There are more results for a decrease in the 5-HIAA levels in depressed patients and in suicides than for 5-HT itself (for review see [1][2][3]46]). Even if some studies reported of increased concentrations of 5-HIAA [26] the majority of studies revealed decreased 5-HT metabolite levels in suicide victims [7,[47][48][49]. Asberg [1] pointed out that in some of these studies, the distribution of CSF 5-HIAA in depressed patients was bimodal.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…There are more results for a decrease in the 5-HIAA levels in depressed patients and in suicides than for 5-HT itself (for review see [1][2][3]46]). Even if some studies reported of increased concentrations of 5-HIAA [26] the majority of studies revealed decreased 5-HT metabolite levels in suicide victims [7,[47][48][49]. Asberg [1] pointed out that in some of these studies, the distribution of CSF 5-HIAA in depressed patients was bimodal.…”
Section: Discussionmentioning
confidence: 97%
“…At present it is not finally evident to what extend the levels measured in the CSF can be seen as representative for the serotonergic transmission [58]. Theoretical and practical aspects of factors influencing postmortem 5-HT or 5-HIAA levels in CSF (Table 2) were summarised by various authors [26,59].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…almost every kind of behavior. In forensic investigation of death, 5-HT has been studied in different body fluids, regarding the cause of death -particularly suicides and drug abuse or as a marker of an acute stress response [2][3][4][5][6][7] with a significant contribution.…”
Section: Introductionmentioning
confidence: 99%